2019
DOI: 10.1042/etls20180177
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven challenges and opportunities in crystallography

Abstract: Structural biology is in the midst of a revolution fueled by faster and more powerful instruments capable of delivering orders of magnitude more data than their predecessors. This increased pace in data gathering introduces new experimental and computational challenges, frustrating real-time processing and interpretation of data and requiring long-term solutions for data archival and retrieval. This combination of challenges and opportunities is driving the exploration of new areas of structural biology, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Despite the higher indexing rate, our overall hI/(I)i is lower than that of 5k2d (Table 1), possibly because of background scattering from the helium path between the crystal and the beam stop (Perutz & Rogers, 1946). Furthermore, it has been shown that acquiring more images can improve the signal-to-noise ratio of the dataset (Glynn & Rodriguez, 2019). In our dataset we used fewer images (16 737) compared with 5k2d (72 753).…”
Section: Discussionmentioning
confidence: 88%
“…Despite the higher indexing rate, our overall hI/(I)i is lower than that of 5k2d (Table 1), possibly because of background scattering from the helium path between the crystal and the beam stop (Perutz & Rogers, 1946). Furthermore, it has been shown that acquiring more images can improve the signal-to-noise ratio of the dataset (Glynn & Rodriguez, 2019). In our dataset we used fewer images (16 737) compared with 5k2d (72 753).…”
Section: Discussionmentioning
confidence: 88%
“…Such joint analytical strategy would not be effective in early years when far fewer protein structures were determined to atomic resolution. Recent rapid growth in protein crystallography, such as in structural genomics (Berman et al, 2012; Bonvin, 2021; Chandonia and Brenner, 2006) and in serial crystallography (Glynn and Rodriguez, 2019; Schaffer et al, 2021), has supplied the necessarily wide sampling of protein structures for a joint analytical strategy to come of age. The vacancies or gaps in a conformational space between well-populated conformational clusters often correspond to less stable transient states whose conformations are difficult to capture, if not impossible.…”
Section: Methodsmentioning
confidence: 99%
“…Such joint analytical strategy would not be effective in early years when far fewer protein structures were determined to atomic resolution. Recent rapid growth in protein crystallography, such as in structural genomics (Chandonia andBrenner, 2006, 2012) and in serial crystallography (Glynn and Rodriguez, 2019;Schaffer et al, 2021), has supplied the necessarily wide sampling of protein structures for a joint analytical strategy to come of age. The vacancies or gaps in a conformational space between wellpopulated conformational clusters often correspond to less stable transient states whose conformations are difficult to capture, if not impossible.…”
Section: Meta-analysis Of Protein Structuresmentioning
confidence: 99%